Axion dark matter from heavy quarks - Aghaie, Mohammad; Armando, Giovanni; Conaci, Angela; Dondarini, Alessandro; Maták, Peter; Panci, Paolo; Šinská, Zuzana; Ziegler, Robert (Physics letters, 2024)
We propose simple scenarios where the observed dark matter abundance arises from decays and scatterings of heavy quarks through freeze-in of an axion-like particle with mass in the 10keV−1MeV range. These models can be tested by future X-ray telescopes, and in some cases will be almost entirely probed by searches for two-body decays K→π+invis. at NA62. As a byproduct, we discuss the cancellation of IR divergencies in flavor-violating scattering processes relevant for thermal axion production, and derive the general contribution to axion-photon couplings from all three light quarks.